PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA SMA MODEL GUIDED INQUIRY UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA MATERI LISTRIK DINAMIS - Al Amin, Rouf; Jatmiko, Budi; Prastowo, Tjipto (Universitas Negeri Surabaya, 2012)
Lack of understanding of the concepts students are not due only to the lack of ability of students to absorb the material submitted by teachers, but also influenced by the ability of teachers to manage teaching and learning activities. Teachers have an important role in the sustainability of good teaching, one of them to set up an exciting learning device so enthusiastic student learning. This study aims to develop learning tools guided inquiry-based high school physics to enhance students' understanding of concepts on the subject of Dynamic Electricity. Development of the 4D model and tested in class X in SMAN 1 Babat odd semester academic year 2012/2013. This research is the development of research trial design using the One Group Pre-test and Post-test Design. Data collection methods used were questionnaires and observation, while the data analysis techniques using quantitative descriptive analysis and qualitative descriptive analysis. The result showed that some of the findings: RPP performing well and a high degree of reliability; activity is the dominant student observation / experiment; students 'understanding of the concept after learning improving students' responses to learning a positive model of guided inquiry. Based on the results of this study concluded that the quality of learning that have developed viable use in teaching to enhance students' understanding of physics concepts. Kurangnya pemahaman konsep siswa tidak disebabkan hanya pada kurangnya kemampuan siswa menyerap materi yang disampaikan guru, tetapi juga dipengaruhi oleh kemampuan guru dalam mengelola kegiatan belajar mengajar. Guru mempunyai peran penting pada keberlangsungan pembelajaran yang baik, salah satunya untuk menyiapkan perangkat pembelajaran yang menarik sehingga siswa antusias mengikuti pelajaran. Penelitian ini bertujuan mengembangkan perangkat pembelajaran fisika SMA berbasis guided inquiry untuk meningkatkan pemahaman konsep siswa pada pokok bahasan Listrik Dinamis. Pengembangan perangkat menggunakan model 4D dan diujicobakan pada siswa kelas X di SMAN 1 Babat pada semester ganjil tahun ajaran 2012/2013. Dari hasil penelitian diperoleh beberapa temuan yaitu: RPP terlaksana dengan baik dan derajat reliabilitas tinggi; aktivitas siswa yang dominan adalah pengamatan/percobaan; pemahaman konsep siswa setelah pembelajaran meningkat; respons siswa terhadap pembelajaran model guided inquiry positif.Berdasarkan hasil penelitian dapat disimpulkan bahwa perangkat pembelajaran yang dikembangkan mempunyai kualitas layak digunakan dalam pembelajaran untuk meningkatkan pemahaman konsep fisika siswa.